Construction of the Meaning of the Swear Word "Anjing" as a Symbol of Intimacy in Komunitas Pecinta Alam Talegong - Asep Kiki Saepul Akbar; Prahastiwi Utari; Ign. Agung Satyawan (Journal of Social Interactions and Humanities, 2022)
This article discusses the change in the meaning of the swear word "Anjing" which is referentially as an insult and refers to the nature of an animal, namely a dog, into a word that is spoken as a sign of intimacy, warmth and closeness among members of an organizational group. This study uses a qualitative approach with the method of observation. Symbolic interaction theory is used to reveal how the word dog is constructed as a symbol of intimacy. The results showed that the word anjing became a symbol of intimacy through high-intensity interaction with the process of interpreting meaning, adjusting and forming institutions in a communal society.